Estimation of ionospheric sporadic E intensities from GPS radio occultation measurements. (June 2018) - Arras, C.; Wickert, J.
Abstract: The radio occultation experiment aboard the FORMOSAT-3/COSMIC satellites enables the observation of phenomena in Earth's ionosphere on a global scale. Numerous radio occultation profiles are used to analyse the occurrence of sporadic E layers as well as its properties. We will present a new method to approach additionally to the presence of sporadic E also its intensity which is closely related to the blanketing frequency ( f b E s ) provided by ionosondes. We observed that the sporadic E occurrence and its intensity show a highly developed annual cycle with high occurrence rates and intensities in the actual summer hemisphere. The global latitude/longitude distribution of both parameters is strongly related to Earth's magnetic field which is reflected by the missing of sporadic E observations along the magnetic equator. Highlights: A new method to extract information of sporadic E layer characteristics from GPS radio occultation data is introduced. Validation with coinciding ionosonde data confirm the new algorithm. We present first global maps of sporadic E intensities.